3D in vitro model for human corneal endothelial cell maturation. (July 2019) - Hutcheon, Audrey E.K.; Zieske, James D.; Guo, Xiaoqing
Abstract: Corneal endothelium is a cellular monolayer positioned on the Descemet's membrane at the anterior cornea, and it plays a critical role in maintaining corneal clarity. Our present study examines the feasibility of utilizing our 3-dimensional (3D) corneal stromal construct, which consists of human corneal fibroblasts (HCF) and their self-assembled matrix, to observe the development and maturation of human corneal endothelial cells (HCEndoCs) in a co-culture model. Three-dimensional HCF constructs were created by growing the HCFs on Transwell membranes in Eagles' minimum essential medium (EMEM) + 10% FBS + 0.5 mM Vitamin C (VitC) for about 4 weeks. HCEndoCs, either primary (pHCEndoC) or cell line (HCEndoCL), were either seeded in chamber slides, directly on the Transwell membranes, or on the 3D HCF constructs and cultivated for 5 days or 2 weeks. The HCEndoCs that were seeded directly on the Transwell membranes were exposed indirectly to HCF by culturing the HCF on the plate beneath the membrane. Cultures were examined for morphology and ultrastructure using light and transmission electron microscopy (TEM). In addition, indirect-immunofluorescence microscopy (IF) was used to examine tight junction formation (ZO-1), maturation (ALDH1A1), basement membrane formation (Laminin), cell proliferation (Ki67), cell death (caspase-3), and fibrotic response (CTGF). As expected, both pHCEndoCs and HCEndoCLs formed monolayers on the constructs; however, the morphology of the HCEndoCLs appeared to be similar to that seen in vivo, uniform and closely packed, whereas the pHCEndoCs remained elongated. The IF data showed that laminin localization was present in the HCEndoCs' cytoplasm as cell-cell contact increased, and when they were grown in the 3D co-culture, the beginnings of what appears to be a continuous DM-like structure was observed. In addition, in co-cultures, ALDH1A1-positive HCEndoCs were present, ZO-1 expression localized within the tight junctions, minimal numbers of HCEndoCs were Ki67-or Caspase-3-positive, and CTGF was positive in both the HCEndoCs cytoplasm and the matrix of the co-culture. Also, laminin localization was stimulated in HCEndoCs upon indirect stimuli secreted by HCF. The present data suggests our 3D co-culture model is useful for studying corneal endothelium maturation in vitro since the co-culture promotes new DM-like formation, HCEndoCs develop in vivo-like characteristics, and the fibrotic response is activated. Our current findings are applicable to understanding the implications of corneal endothelial injection therapy, such as if the abnormal DM has to be removed from the patient, the newly injected endothelial cells will seed onto the wound area and deposit a new DM-like membrane. However, caution should be observed and as much of the normal DM should be left intact since removal of the DM can cause a posterior stromal fibrotic response. Highlights: Endothelial cells form a monolayer on 3D constructs, similar to in vivo. DM-like structure was observed when endothelial cells were grown on the 3D constructs. Endothelial cells matured in co-culture as seen by ALDH1A1 and ZO-1 localization. Endothelial cells activated the fibrotic response in 3D constructs in co-culture. Cell communication occurs through direct contact and indirect stimuli.